2014
DOI: 10.1007/s00441-014-1918-5
|View full text |Cite
|
Sign up to set email alerts
|

The roles of calcium-sensing receptor and calcium channel in osteogenic differentiation of undifferentiated periodontal ligament cells

Abstract: Elevated extracellular calcium has been shown to promote the differentiation of osteoblasts. However, the way that calcium affects the osteogenic differentiation of human periodontal ligament stem/progenitor cells (PDLSCs) remains unclear. Our aim has been to investigate the proliferation and osteogenic differentiation of a calcium-exposed human PDLSC line (cell line 1-17) that we have recently established and to elucidate the roles of the calcium-sensing receptor (CaSR) and L-type voltage-dependent calcium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Also, NPS2143 decreased the protein level of CaSR in the presence of MTA. It has been demonstrated previously that exogenous calcium stimuli increased the expression of CaSR in mammary gland epithelial cells 30) and periodontal ligament cells 17) . These findings were consistent with our results.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Also, NPS2143 decreased the protein level of CaSR in the presence of MTA. It has been demonstrated previously that exogenous calcium stimuli increased the expression of CaSR in mammary gland epithelial cells 30) and periodontal ligament cells 17) . These findings were consistent with our results.…”
Section: Discussionmentioning
confidence: 84%
“…Comparable effects have been observed in bone marrow-derived progenitor cells 21) , preadipocytes 22) , and periodontal ligament cells 17) . These findings suggest the presence of a mechanism involving CaSR expression on the cell membrane responding to local changes in calcium ion concentrations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the same study, the authors reported evidences demonstrating that the signaling pathway between extracellular Ca 2+ and bone morphogenetic protein 2 (BMP-2), a protein essential to maintain bone homeostasis and having a prominent role in fracture healing, involves type L voltage-dependent Ca 2+ channels (L-VDCC) rather/more than CaSR. A subsequent study strengthen the role of CaSR in supporting osteogenic differentiation, as it demonstrated that extracellular calcium promotes osteogenic differentiation in human periodontal ligament stem/progenitor cells and that CaSR and L-VDCC appear to act reciprocally in mediating this process [63]. In ovine amniotic fluid MSCs, increasing [Ca 2+ ] o was reported to increase ALP activity [49].…”
Section: Discussionmentioning
confidence: 89%
“…However, the presence of CaSR in bone-forming cells is controversial 108 , and osteoblasts derived from CaSR-null mice remained to possess osteogenic differentiation potential 109,110 . Further, another study demonstrated that inhibition of CaSR further induced, rather than suppressed, Ca 2+ -mediated osteogenic differentiation 111 , suggesting that CaSR is dispensable in osteogenic differentiation and mineralization.…”
Section: Molecular Perspectives: Common Properties Of Pulp-cappimentioning
confidence: 97%